2010
DOI: 10.5851/kosfa.2010.30.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Biologically Active Substances and Antioxidant Activity of New Zealand Deer Velvet Antler Extracts

Abstract: Deer velvet antler was subjected to the extraction process using boiling water at three different temperatures (100, 110 and 120 o C) and 70% ethanol solution. Functional components such as uronic acid, sulfated-glycosaminoglycans (sulfated-GAGs) and sialic acid in the extracts were analyzed, and their antioxidant activities were investigated using several in vitro models. Uronic acid and sulfated-GAGs content of each extract significantly decreased with increasing extraction temperature (p<0.05), while the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…These results suggest that the main ingredients of VAPH are protein and uronic acid (an acidic polysaccharide). The sialic acid content of the VAPH obtained in this study was similar to that observed by Je et al (2010[ 9 ]), who used hot water extracts. However, the sulfated-GAG and uronic acid contents in VAPH were higher than those from the hot water extracts.…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that the main ingredients of VAPH are protein and uronic acid (an acidic polysaccharide). The sialic acid content of the VAPH obtained in this study was similar to that observed by Je et al (2010[ 9 ]), who used hot water extracts. However, the sulfated-GAG and uronic acid contents in VAPH were higher than those from the hot water extracts.…”
Section: Discussionsupporting
confidence: 91%
“…Hydroxyl radicals are extremely reactive and easily react with amino acids, DNA, and membrane components. In this study, the hydroxyl radical scavenging activity of RVA was higher than that of velvet antler as reported by Je et al [32]. In addition, our analysis of ABTS radical scavenging activity by RVA identified activity higher than that reported by Zhao et al [33].…”
Section: Antioxidant Activitysupporting
confidence: 69%
“…To date, some studies have been conducted to determine the antioxidant activity and chemical compositions in the New Zealand velvet antler (NZVA; Je et al, 2010 ) and RVA ( Je et al., 2011 ), and bioactive compounds in Chinese VA extract ( Zhang et al, 2019 ). However, it still remains unknown whether there are some differences existing in biological activity, chemical composition, flavor and bioactive compounds between the Korean and the imported VA products.…”
Section: Introductionmentioning
confidence: 99%